MEWUJUDKAN KAWASAN BEBAS ASAP ROKOK (KBAR) DENGAN PEMBUATAN POJOK ROKOK DI KELURAHAN SONDAKAN - Darah Ifalahma; Ana Yuliana; Anik Sulistiyanti; Nila Khoirunnisa Syamtari; Herni Safitri (LPPM Universitas Bina Bangsa, 2024)
Smoking behavior is behavior that is considered normal for the majority of citizens in Indonesia. From year to year the number of smokers in Indonesia is increasing, especially among the young population. Based on 2018 Basic Health Research (Riskesdas) data, the prevalence of smokers aged 10-18 years was 9.1%. In an effort to regulate smoking behavior and protect passive smokers from the negative impacts of smoking behavior, a No-Smoking Area (KTR) has been established based on Health Law number 36 of 2009. A No-Smoking Area is an area that is declared prohibited for smoking or producing, selling, advertise, and/or promote Tobacco Products. The areas that constitute KTR according to the Health Law are health service facilities; place for teaching and learning processes; a place for children to play; worship place; public transportation; workplace; and public places. From the results of data collection from the Healthy Indonesia Family Approach Program (PISPK) in the Pajang Community Health Center area in RW 09 Sondakan Laweyan Surakarta, a community problem was found, namely smoking. Public knowledge about smoking is still low and self-awareness in implementing smoking ethics is also low. The aim of this activity is to increase the knowledge of the people of RW 09 Sondakan Subdistrict about smoking ethics and to create a Smoke Free Area (KBAR) by creating a Cigarette Corner. The method used is providing education to residents in the form of health education about smoking ethics and activating Cigarette Corners. The result of this activity was that there was an increase in respondents' knowledge between before and after being given the counseling. Increased knowledge score by 35%. At the end of the activity, residents understood the ethics of smoking and were committed to realizing a KBAR (Smoke Free Area) by utilizing the Cigarette Corner